Effect of the incorporation of salted additives on probiotic whey cheeses. (1st June 2015) - Madureira, Ana Raquel; Soares, José C.; Pintado, Manuela E.; Gomes, Ana M.P.; Freitas, Ana Cristina; Xavier Malcata, F.
Abstract: The research effort described here has focused on incorporation of Lactobacillus casei, in whey protein matrices, in the presence of selected salty additives. Those matrices were produced via thermal processing of a combination of either ovine or bovine whey (or a mixture thereof) with ovine milk, and were inoculated (at 10%) with L. casei strain LAFTI ® L26; salt, salt and herbs, or salt and xanthan were further added to such matrices, which were then homogenized and stored at 7 °C for up to 21 d. In general, viable cell numbers maintained or even increased throughout the storage period, irrespective of the type of salty additive considered. Partial depletion of lactose was detected, and concomitant production of lactic acid throughout the 21 d-period of storage; lower lactic acid concentrations were found in matrices containing salty additives. In matrices with xanthan (SX), the probiotic strain exhibited the lowest metabolic activity. Matrices SX were less soft and firmer than the others, by the end of storage, and were similar to matrices with herbs (SH). The incorporation of salty additives affected bacterial metabolism, in terms of glycolysis and proteolysis, which in turn had a significant impact on the development of textural properties.